ANALISIS POTENSI PRODUK MUSYARAKAH TERHADAP PEMBIAYAAN SEKTOR RIIL UMKM - Trimulato, Trimulato (Universitas Muhammadiyah Yogyakarta, 2017)
Shariah banking in Indonesia is growing to continued, seen from the account of customers continues to grow. By 2016 the market share of shariah banking has reached 5 percent translucent. The presence of Act Number 21, 2008 concerning shariah banking strengthens presence in shariah. In terms of financing in shariah banking still dominated by the financing by buying and selling is not for the profit sharing. Contributions of Musyarakah financing achieve 105,112,000,000,000 or by 62.29% of the total financing. While the financing agreement for the results of the identity of shariah banking only contributed 34.44% or Rp 58,123,000,000,000. This paper uses a descriptive qualitative. Limitations in this paper is focused on products with contract Musharakah financing in shariah banking and real sector SMEs. This paper uses literature study from various sources. The results of this paper that the potential development of financing products with musyarkah contract in shariah banking is still very large. Growth in the use Musyarakah decreased in 2016 which grew only 13.79%. While credit growth to SMEs is still low does not exceed 20%. It is seen that the account of SMEs continues to grow, then the portion of Musharakah financing products are still small. This indicates that the product Musharakah financing in shariah banking are very suited to the conditions and character of SMEs.